Is there an association between metabolic syndrome and drug resistance in patients with epilepsy? - Afshan Davari; Amir Reza Bahadori; Azadeh Imeni Kashan; Mehrdad Sheikhvatan; Sara Ranji; Sajad Shafiee; Abbas Tafakhori (Medicine, 2026)
Epilepsy is one of the most prevalent neurological disorders, affecting approximately 1% of the population, with one-third of patients developing drug-resistant epilepsy (DRE). In addition, metabolic syndrome (MetS), through inflammation and oxidative stress mechanisms, may influence epilepsy outcomes. The main objective of the current study is to determine the prevalence of MetS among patients with epilepsy (PWE) and evaluate its association with DRE. This cross-sectional study was conducted between March and October 2024 at a regional hospital in Tehran, involving 180 PWE aged 18 to 70 years. Participants were classified into well-controlled epilepsy and DRE groups based on the International League Against Epilepsy criteria. MetS was also diagnosed using the International Diabetes Federation guidelines. Data were analyzed using SPSS software, which illustrated that MetS was present in 33.8% of participants, with a significantly higher prevalence in well-controlled epilepsy patients (47.7%) compared with those with DRE (20%, P < .001), and it played a role in predicting response to treatment in PWE. Furthermore, body mass index, waist circumference, and blood pressure were significantly higher in the well-controlled group ( P = .012 and P = .007, respectively). MetS was more prevalent in well-controlled epilepsy patients and was associated with a decreased risk of DRE. However, further research is needed to explore the relationship between MetS and DRE.